A novel method of complex evaluation of meibomian glands morphological and functional state - V. N. Trubilin (Oftalʹmologiâ, 2014)
A novel method that provides complex assessment of meibomian glands morphological and functional state — biometry of meibomian glands — was developed. The results of complex examination (including meibomian glands biometry), correlation analysis data and clinical findings demonstrate direct association between the objective (i.e., meibomian glands dysfunction by biomicroscopy, tear film break-up time / TBUT, symptomatic TBUT, compression testing) and subjective signs of meibomian glands dysfunction (patient’s complaints) and the parameters of meibomian glands biometry. High direct correlation between biometrical index and compression test result was revealed (p = 0.002, Spearman’s rank correlation coefficient = 0.6644). Meibomian glands dysfunction is characterized by biometric parameters abnormalities, i.e., dilatation of meibomian glands orifices, decrease of distance between meibomian glands orifices, partial or total atrophy of meibomian glands (even up to gland collapse with its visual reduction and increase of distance between the glands). The suppression of inflammatory process and the recovery of meibomian glands secretion improve biometric parameters and result in the opening of meibomian glands orifices, liquefaction of clogs, evacuation of meibomian glands secretion, narrowing of meibomian glands orifices and increase of distance between them. The proposed method expands the armamentarium of meibomian glands dysfunction and lipid-deficient dry eye diagnosing. Meibomian glands biometry can be applied in specialized ophthalmological hospitals and outpatient departments. It is a simple procedure of short duration that does not require any special equipment or professional skills. Meibomian glands biometry enables to prescribe pathogenically targeted therapy and to improve quality of life.